dx | ||
Podstaw arcsinx = t , | , x = sint | |
√1−x2 |
x | x | |||
∫ | (xarcsin(x))dx=−x√1−x2arcsin(x)+∫√1−x2(arcsin(x)+ | )dx | ||
√1−x2 | √1−x2 |
x | ||
∫ | (xarcsin(x))dx=−x√1−x2arcsin(x)+∫√1−x2arcsin(x)dx+∫xdx | |
√1−x2 |
x | 1−x2 | x2 | ||||
∫ | (xarcsin(x))dx=−x√1−x2arcsin(x)+∫ | arcsin(x)dx+ | ||||
√1−x2 | √1−x2 | 2 |
x2 | x2 | arcsin(x) | ||||
2∫ | arcsin(x)=−x√1−x2arcsin(x)+ | +∫ | dx | |||
√1−x2 | 2 | √1−x2 |
x2 | x2 | arcsin2(x) | ||||
2∫ | arcsin(x)=−x√1−x2arcsin(x)+ | + | +C1 | |||
√1−x2 | 2 | 2 |
x2 | 1 | x2 | arcsin2(x) | |||||
∫ | arcsin(x)=− | x√1−x2arcsin(x)+ | + | +C | ||||
√1−x2 | 2 | 4 | 4 |